2021
DOI: 10.1021/acsenergylett.1c00970
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical p-Doping of CsPbBr3 Perovskite Nanocrystals

Abstract: Lead halide perovskite nanocrystals have drawn attention as active light-absorbing or -emitting materials for opto-electronic applications due to their facile synthesis, intrinsic defect tolerance, and color-pure emission ranging over the entire visible spectrum. To optimize their application in, e.g., solar cells and light-emitting diodes, it is desirable to gain control over electronic doping of these materials. However, predominantly due to the intrinsic instability of perovskites, successful electronic dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…89 Doping of trivalent ions at the B site, e.g. in CsPbI 3 done by Pradhan et al, 90,91 increases the interaction of ions with the crystal frame which may add to the stability of the perovskite structure avoiding the need for functionalization, and does not necessarily compromise the optoelectronic performance. However even cation doped CPQD modifications have only helped with little more environmental resistance in general and still possess all the undesirable properties that do not allow them to be dispersed in water or biological medium.…”
Section: Surface Passivationmentioning
confidence: 99%
“…89 Doping of trivalent ions at the B site, e.g. in CsPbI 3 done by Pradhan et al, 90,91 increases the interaction of ions with the crystal frame which may add to the stability of the perovskite structure avoiding the need for functionalization, and does not necessarily compromise the optoelectronic performance. However even cation doped CPQD modifications have only helped with little more environmental resistance in general and still possess all the undesirable properties that do not allow them to be dispersed in water or biological medium.…”
Section: Surface Passivationmentioning
confidence: 99%
“…CsPbBr 3 is weakly p type when grown in halide-rich conditions, , but the carrier densities are low because the Fermi level is still hundreds of meV above the valence-band maximum (VBM). Electrochemical doping has shown that moderate electron or hole densities can be achieved in thin films of nanocrystals, , but an effective and reliable acceptor dopant is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Conductivity increases were also observed in the oxidation direction, similar to the one recently reported. 30 However, the conductivity increase in the bulk film was 5 times less than that of NC film probably from limited accessible electrolyte ions for charge compensation (Figure S9).…”
mentioning
confidence: 98%
“…Jiang et al reported Li + doping in CsPbBr 3 films and improved LED performance, while the stability of the perovskites remains in question . Recently, Mulder et al have reported electrochemical p-type doping of long ligand-based CsPbBr 3 NC thin films and mentioned that n-doping of CsPbBr 3 via an electrochemical method is not possible owing to facile Pb II reduction to Pb 0 . Considering that the electrochemical response of NC thin films depends sensitively on the film fabrication and synthetic method, , the possibility of electrochemical n-doping of CsPbBr 3 NC films should be judiciously approached.…”
mentioning
confidence: 99%